KAJIAN KUALITAS AIR DAN STATUS MUTU AIR SUNGAI METRO DI KECAMATAN SUKUN KOTA MALANG - Ali, Azwar (Bumi Lestari, 2013)
Abstract Metro River is utilized by society who lives along the river in order to fulfill their daily needs, such as public bathing, washing, and toilet facilities, irrigation for agriculture, disposal for garbage and water domestic waste, the use of water would reduce water quality of the river. Objectives of the research were to find out and analyze condition of water quality of the river and water quality status in Metro River, as well as its suitability to water quality standard according to its purpose. Determination of the sample-collecting spots has applied purposive sampling method, while water sample has been taken using grab sample method. Water quality analysis used the prevailing standard method and water quality status was determined by Pollution Index method. Result of the research showed that water quality in Metro River, for DO parameter in station 3, was below the quality standard according to its purpose and for BOD parameter in station 2 and 3, it was beyond the standard of water quality according to its purpose, for class III. Meanwhile, quality of water in Metro River from upstream to the downstream has been decreasing as shown by the increasing value of PI, water quality status in station 1 and 2 showed “excellent condition”, and the station 3 showed “mild polluted”.
Keywords: Key words : Water, River, Water Quality, Water Quality Status, Water Quality Standard